1991
DOI: 10.1016/0741-5214(91)90010-r
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study of cerebrospinal fluid drainage to prevent paraplegia after high-risk surgery on the thoracoabdominal aorta

Abstract: This article is concerned with the study of the effect of several variables, principally that of cerebrospinal fluid drainage, on the incidence of neurologic deficit in a prospective randomized series of patients with extensive aneurysms of the descending thoracic and abdominal aorta (thoracoabdominal type I and II). Forty-six patients had cerebrospinal fluid drainage, and 52 were controls, with a total of 98 available for study. Cerebrospinal fluid pressure was continuously monitored in the former group and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(44 citation statements)
references
References 14 publications
0
44
0
Order By: Relevance
“…Since all of our patients are still alive, we are unable to verify our clinical data with regard to actual pathology of the grey and white matter. Crawford et al 4 showed with MRI scanning, 10 days after the onset of the de®cit, involvement of the grey matter. These ®ndings were noted in those patients who had more profound de®cits and were associated with a poor prognosis for signi®cant recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since all of our patients are still alive, we are unable to verify our clinical data with regard to actual pathology of the grey and white matter. Crawford et al 4 showed with MRI scanning, 10 days after the onset of the de®cit, involvement of the grey matter. These ®ndings were noted in those patients who had more profound de®cits and were associated with a poor prognosis for signi®cant recovery.…”
Section: Discussionmentioning
confidence: 99%
“…On another hand, Gharagozloo et al 30 considers that the neural lesion depends on four main factors: decrease in spinal cord blood¯ow, rate of neuronal metabolism, post ischaemia reperfusion injury and post perfusion blood¯ow. Some particular measures have to be emphazised to allow: the best conditions for blood¯ow, depending on the localisation and duration of the cross-clamping 29 , by a shunt or a pulsatile bypass 2 , by CSF drainage 4 and local injection of papaverine; the protection of regional arteries by the preoperative localisation 28,31 and preoperative reimplantation; the monitoring of function of spinal pathways by somatosensory potentials, and electrospinogram, as proposed Stulmeier et al 32 , or better, by the monitoring of spinal re¯exes; a chemical protection 3,30 by superoxyde-dismutase, calcium-channels blockers, NMDA-receptors antagonists, barbiturates, steroids, naloxone and other agents, represents only an approach to reduce the lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They receive blood from radicular arteries which originate in the aorta. The PSA also receives a relatively luxuriant blood flow from the intercostal arteries while the ASA receives a much more limited blood flow from the radicular arteries off the aorta [ 21 ] . The ASA blood supply by spinal cord region:…”
Section: Motor Pathway Blood Supplymentioning
confidence: 99%
“…Based on the results of these experiments, the concept of CSF drainage has been applied clinically. Crawford et al [44] performed a prospective randomized study on the effectiveness of CSF drainage for preventing paraplegia and reported that it was not beneficial in this regard. Conversely, a more recent prospective randomized study of CSF drainage by Coselli et al, [45] and a report by Safi et al, [46] showed that CSF drainage did help to prevent spinal cord injury.…”
Section: Cerebrospinal Fluid Drainagementioning
confidence: 99%